(untitled) (Scientific journal of the Fergana State University, 2024)
The article contains considerations such as the production process of higher education, measures to encourage critical thinking, and the development of skills that are relevant to society and determined by its needs. A number of observations about the priority areas of national culture, formed in the interaction of general education, in particular vocational and higher education, have also been identified. This place presents proposals and conclusions on the basics of organizing global education and improving human rights, social responsibility and gender equality in its development, we were talking about ideas that provide basic fundamental understanding when analyzing the direction of exit. As a result of this, it was expressed that residents have become more educated, confident and responsible citizens, as a result of which the development of necessary knowledge and concepts and certain skills, which is an important part of global education, contributes to the formation of attitudes at one level or another towards certain events.